Motivations of wheelchair curling athletes to participate in sport: a qualitative research - Daşkesen, Sonay Serpil; Bedir, Deniz; İlhan, Ekrem Levent; Onur, Tuğba Demir; Mair, Heather (Frontiers in Psychology, 2025)
IntroductionSelf-Determination Theory (SDT) is a holistic approach that provides a comprehensive framework for understanding individuals’ intrinsic and extrinsic motivations, analyzing the nature of motivation and its relationship with psychological development. This study employs the SDT framework to examine the motivational processes of wheelchair curling athletes.MethodsThis qualitative study involved eleven wheelchair curling athletes. Data were collected through a personal information form and semi-structured interviews. The collected data were analyzed using thematic analysis, and themes related to athletes’ motivational experiences were identified.ResultsThe findings revealed that the motivation of wheelchair curling athletes to participate in sport is influenced by both intrinsic and extrinsic factors. Intrinsic motivation, nourished by physical, emotional, and social sources, strengthens athletes’ participation in curling, enhances their enjoyment, and reinforces their commitment to the sport. In contrast, extrinsic motivation is shaped by elements such as external regulation, introjected regulation, identified regulation, and integrated regulation. However, a motivation mainly stems from lack of resources and organizational deficiencies, which negatively affect athletes’ participation in and continuity of the curling sport.DiscussionThe study emphasizes the importance of individual and structural factors influencing the motivation of wheelchair curling athletes. Strengthening organizational support and improving resource accessibility can enhance athletes’ intrinsic motivation, thereby promoting participation and sustainability in adapted sports.